Selection of maize lines for estimating combining ability in topcrossings - G. Ya. Krivosheev; A. S. Ignatiev (Зерновое хозяйство России)
Hybrid maize breeding is carried out based on interline hybridization using heterosis in the first generation. Hybridization efficiency can be increased using parental forms with high combining ability in crosses. The purpose of the study was to identify new self-pollinated lines of maize with high general and specific combining ability, to identify the impact on the accuracy of the estimation of related lines included in the study. The current study was carried out at the FSBSI Agricultural Research Center «Donskoy» in 2021 and 2022. The objects of the study were two testers PD 329, KV 399 and 10 self-pollinated lines, including two lines (KV 410 and DS 22/325) related to tester PD 329, twenty topcross maize hybrids. The method for estimating combining ability was complete topcrosses. Estimation of new self-pollinated lines by the topcross method made it possible to identify the lines ‘KV 498’ and ‘DS 498/203-3’ with a consistently high overall combining ability according to the trait ‘grain productivity’. The specific combining ability was characterized by variability depending on the year of study. Only the line ‘KV 401’ had a high SCR in all years of study. The inclusion of lines related to the testers in the set had no effect or only slightly affected the estimates of the TCS of the remaining unrelated lines. The effect on the SCS was not significant, however, the estimation of the SCS would be more accurate if related lines were excluded from the set. There have been identified such new testcross hybrids with large grain productivity as ‘PD 329 × KV 498’ (3.92 t/ha), ‘KV 399 × KV 498’ (4.71 t/ha),‘KV 399 × KV 401’ (4.80 t/ha), ‘KV 399 × DS 498/203-3’ (4.60 t/ha). They were obtained with the participation of new lines characterized by high general or specific combinative ability, which can be recommended to be included in crossbreeding programs to develop highly heterotic maize hybrids.